State of mood, motivation, and impulsivity of young athletes: a cross-sectional study - Karla Medeiros Costa; Claudio Andre Barbosa De Lira; Eduardo Macedo Penna; Marília Santos Andrade; Fabiano De Suza Fonseca; Dalton De Lima-Junior; Paulo Gentil; Alberto Souza Sá Filho; Gustavo De Conti Texiera Costa (Termedia Publishing House, 2022)
Purpose The aim of the study was to compare the mood, motivation, and impulsivity of young athletes of different sexes and ages. Methods The sample consisted of 147 young student-athletes of both sexes, aged 12-17 years, participating in the regional stage of the Brazilian Youth School Games 2018. The individuals were categorized into 4 groups for analysis considering sex (male vs. female) and age (≤ 14 years and ≥ 15 years). Results (1) Female athletes aged ≤ 14 years demonstrated greater instability of mood compared with males of the same age ( p = 0.009). (2) Female athletes aged ≥ 15 years presented less energy and disposition than female athletes aged ≤ 14 years ( p = 0.007) and males aged ≥ 15 years ( p = 0.001). (3) Both female groups (aged ≤ 14 years and ≥ 15 years) had a higher score than the male group aged ≤ 14 years for lack of perseverance ( p = 0.003 and p = 0.034, respectively) and lack of premeditation ( p = 0.012 and p = 0.013, respectively). Conclusions The mood, motivation, and impulsivity of young athletes have varying characteristics in males and females and these variables are modulated by age.